Analisis Penerapan Sistem Pengendalian Internal dalam Menunjang Efektivitas Pemberian Kredit : (Studi Kasus pada Koperasi Kredit Sangosay Cabang Kupang) (Jurnal Kendali Akuntansi, 2025)
The sangosay cooperative is one of the financial institutions engaged in the field of savings and loans providing loan facilities. Where this is the function of cooperatives to support progress and support economic growth. This research was conducted on the Sangosay Cooperative Kupang Branch which carries out savings and loan activities that are quite healthy, starting from an increase in the number of members, borrowers and bad loans. So the purpose of this study is to see the implementation of the internal control system implemented by the Sangosay Credit Cooperative Kupang Branch in supporting the effectiveness of credit provision. The research approach is qualitative descriptive research. collection techniques in two ways: literature study and field. The results of the study concluded that the internal control system implemented by the Kupang Branch Sangosay Cooperative according to COSO which consists of five elements with components in it are running quite well, Supporting factors related to the implementation of the internal control system in the Kupang Branch Sangosay Credit Cooperative are transparency and accountability while the inhibiting factor is the lack of employees.